The role of sucrose in maintaining pollen viability and germinability in Corylus avellana L.: a possible strategy to cope with climate variability - C. Brandoli; A. Mortada; C. Todeschini; C. Siniscalco; E. Sgarbi (Protoplasma, 2025)

Implementation of IUCN criteria for the definition of the Red List of Ecosystems in Italy - G. Capotorti; L. Zavattero; R. Copiz; E. Del Vico; L. Facioni; S. Bonacquisti; R. Frondoni; M. Allegrezza; F. Attorre; G. Bacchetta; E. Barni; E. Biondi; et al. (Plant Biosystems, 2020)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Decomposition processes interacting with microtopography maintain ecosystem heterogeneity in a subalpine grassland - L. Oddi; L. Celi; E. Cremonese; G. Filippa; M. Galvagno; G. Palestini; C. Siniscalco (Plant and Soil, 2019)

Distribution map of Ambrosia artemisiifolia L. (Asteraceae) in Italy - R. Gentili; F. Gilardelli; E. Bona; F. Prosser; A. Selvaggi; A. Alessandrini; F. Martini; P. L. Nimis; T. Wilhalm; M. Adorni; N. M. G. Ardenghi; E. Barni; et al. (Plant Biosystems, 2017)

From plant traits to invasion success: Impacts of the alien Fallopia japonica (Houtt.) Ronse Decraene on two native grassland species - T. Mincheva; E. Barni; C. Siniscalco (Plant Biosystems, 2016)

Short-term signals of climate change in Italian summit vegetation: observations at two GLORIA sites - A. Stanisci; L. Frate; U. Morra Di Cella; G. Pelino; M. Petey; C. Siniscalco; M. L. Carranza (Plant Biosystems, 2016)

Monitoring and modeling the invasion of the fast spreading alien Senecio inaequidens DC. in an alpine region - G. Vacchiano; E. Barni; M. Lonati; D. Masante; A. Curtaz; S. Tutino; C. Siniscalco (Plant Biosystems, 2013)

A global view of the OCA2-HERC2 region and pigmentation - Michael P. Donnelly; Peristera Paschou; Elena Grigorenko; David Gurwitz; Csaba Barta; Ru-Band Lu; Olga V. Zhukova; Jong-Jin Kim; Marcello Siniscalco; Maria New; Hui Li; Sylvester L. B. Kajuna; et al. (Human Genetics, 2012)

Non-native species distribution along the elevation gradient in the western Italian Alps - C. Siniscalco; E. Barni; G. Bacaro (Plant Biosystems, 2011)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Syntaxonomy, synecology and conservation of Pseudostellaria europaea Schaeftlein communities in NW Italy in comparison with populations in the Eastern Alps - M. Lonati; C. Siniscalco (Plant Biosystems, 2009)

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

Plant and lichen colonization in an asbestos mine: Spontaneous bioattenuation limits air dispersion of fibres - S. E. Favero-Longo; C. Siniscalco; R. Piervittori (Plant Biosystems, 2006)

AirborneCorylus pollen monitoring: Preliminary data - R. Caramiello; V. Polini; C. Siniscalco; L. Radicati Di Brozolo; G. Me (Aerobiologia, 1987)

Schede palinologiche diArtemisia vulgaris L.,Artemisia verlotorum Lamotte;Artemisia annua L., su campioni freschi e acetolizzati - R. Caramiello; R. Ferrando; C. Siniscalco; V. Polini (Aerobiologia, 1987)